UPAYA MENINGKATKAN KUALITAS BELAJAR PESERTA DIDIK DI SEKOLAH DASAR NEGERI 01 PALAPA BANDAR LAMPUNG - Murni, Sri; Sari, Permata; Rimonda, Rubi (LPPM STKIP PGRI Bandar Lampung, 2020)
This study aims to 1. Know the conditions of the school environment that affect the quality of student learning. 2. Knowing the picture quality of students in learning. 3. Influence of inadequate state of confusion for students. In this case, the facilities and infrastructure are inadequate so that the quality of student learning is limited, such as the division of morning and afternoon classes and teacher rooms that are still less effective. The importance of the role of counselling guidance teacher to explore the potential of students who have high-quality learning. In this case, the BK teacher in the elementary school 1 palapa Bandar Lampung does not yet exist and how the role of the BK teacher is replaced by the homeroom teacher who understands students in the development and the problems faced by these students. The results of this study indicate that the effectiveness of student learning and the role of the BK teacher is still lacking. Data collection techniques in this case we use interview techniques.